PENERAPAN PERMAINAN ULAR TANGGA DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PADA ANAK KELOMPOK B TK AISYIYAH BUSTANUL ATHFAL 85 LEGOSO CIPUTAT TIMUR - Wati Sukmawati; Sintha Wahjusaputri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2017)
In the perspective of Islam, education must be obliged throughout life. Researchers seek to find solutions to problems using Action Research (PTK) by treatment of 2 (two) cycles, with the adoption of snakes and ladders game. In the reality on the ground were identified from 21 the number of children in group B, only 6 or 33% have the ability in the areas of math, while 14 children or 67% still need the help of a teacher. The learning process is still centered on the teacher, using the lecture method and administration tasks, monotonous and tend to be conventional. The results showed that through the game of snakes and ladders can increase the child's ability to count, and results from the growing percentage in sequencing numbers and put the emblem in accordance with the number of object numbers